THE STATE OF ART IN GENDER - WOMEN - IN EDUCATION IN THE STATE OF SAO PAULO - Ribeiro, Ana Paula [UNESP]; Rossi, Celia Regina [UNESP] (Fundacao Univ Tocantins, 2017)
The article demonstrates the results, understandings and concerns of a research done by one of the authors, on his graduation. The study intention was to identify, through a theoretical and bibliographic method, the construction of gender identity - woman - from an educational perspective. In order to do this, abstracts analysis were performed with ten doctoral dissertations and ten master thesis, all stored on CAPES database and presented in the last ten years in the state of Sao Paulo. In spite of the increasing visibility of the female gender in the labor market, in school institutions and in their conquest of independence, cases of violence, low salaries, prejudice, misogyny and stereotypes, are still in force today. About education, it is clear that there is still a strong devaluation towards women, minimizing the work done in schools, relegation to academic knowledge of the exact sciences area and also a strong struggle for the conquest of Rights denied.
Keywords: Gender; Sexuality; Woman; Education